1986
DOI: 10.1891/0886-6708.1.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Coercive Sexual Behavior in a Nonclinical Sample of Males

Abstract: The sexual coercion literature has suggested numerous factors related to aggressive sexual behavior. The present investigation explores a number of these factors in a community sample. Data collected from 189 volunteers from the community included measures of sexual arousal, social perception, personality variables, attitudes toward women, and self-reported likelihood to rape. Multiple-regression analyses were used to determine the relative association of these factors to coercive sexual behavior. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 0 publications
5
50
0
Order By: Relevance
“…Until the 1970s, explanations of rape were dominated by a psychopathology model. Under the psychopathology model, rape is viewed as a symptom of a psychiatric disorder (Murphy, Coleman, & Haynes, 1986). Therefore, rapists are viewed as deviants who do not represent what society views as "normal"…”
Section: Date Rapementioning
confidence: 99%
“…Until the 1970s, explanations of rape were dominated by a psychopathology model. Under the psychopathology model, rape is viewed as a symptom of a psychiatric disorder (Murphy, Coleman, & Haynes, 1986). Therefore, rapists are viewed as deviants who do not represent what society views as "normal"…”
Section: Date Rapementioning
confidence: 99%
“…In addition, Pollard (1994) cited 10 more studies, which found Burts' RMA, AIV, and ASB scales to be associated with self-reported LR, the SES, or both. An exception is the study of Murphy, Coleman, and Haynes (1986) with a community sample, in which scores on the RMA, ASB, and SRS scales were found to be unrelated to self-rated LR.…”
Section: Attitudes and Beliefsmentioning
confidence: 99%
“…Murphy et al (1986) tested this hypothesis in a community sample. Participants were shown videotaped interactions in which men initiated social interactions with women.…”
Section: Perception Of Women's Communicationsmentioning
confidence: 99%
See 2 more Smart Citations